Rural areas in Poland: Educational attainment vs. level of economic development - Kamińska, Wioletta (Wydział Nauk Geograficznych i Geologicznych Uniwersytetu im. Adama Mickiewicza, 2013)
The aim of this article is to analyse relations between the educational attainment of the rural population and the level of economic development of the rural areas in Poland. A typology of communes in terms of the analysed relations is made. This is the first research of this type involving all the rural areas in Poland conducted at the level of the commune. The research has shown a significant linear relation between the educational attainment of the population and the level of economic development of rural areas. The correlation coefficient amounts to 0.565.
Keywords: rural areas; education; economic development; communes